Acoustic Scattering Problems with Convolution Quadrature and the Method of Fundamental Solutions (Communications in Computational Physics, 2021)
Time-domain acoustic scattering problems in two dimensions are studied.The numerical scheme relies on the use of the Convolution Quadrature (CQ) methodto reduce the time-domain problem to the solution of frequency-domain Helmholtzequations with complex wavenumbers. These equations are solved with the methodof fundamental solutions (MFS), which approximates the solution by a linear combination of fundamental solutions defined at source points inside (outside) the scatterer forexterior (interior) problems. Numerical results show that the coupling of both methodsworks efficiently and accurately for multistep and multistage based CQ.